2006
DOI: 10.1111/j.1365-2265.2006.02612.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated 18F‐FDG PET/CT for the initial evaluation of cervical node level of patients with papillary thyroid carcinoma: comparison with ultrasound and contrast‐enhanced CT

Abstract: Our preliminary results suggest that integrated PET/CT does not provide any additional benefit when compared to US and CECT for the initial evaluation of cervical node levels in patients with papillary thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
6
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 29 publications
(87 reference statements)
4
90
6
4
Order By: Relevance
“…Three previous studies have evaluated the diagnostic accuracy of FDG PET in N staging of thyroid cancer (Table 1; Jeong et al 2006a, Morita et al 2010, Choi et al 2011b. LN metastases of thyroid cancer are found most commonly in the central neck compartment (Ferris et al 2012).…”
Section: Preoperative Assessment Of Thyroid Cancer With Fdg Petmentioning
confidence: 99%
See 2 more Smart Citations
“…Three previous studies have evaluated the diagnostic accuracy of FDG PET in N staging of thyroid cancer (Table 1; Jeong et al 2006a, Morita et al 2010, Choi et al 2011b. LN metastases of thyroid cancer are found most commonly in the central neck compartment (Ferris et al 2012).…”
Section: Preoperative Assessment Of Thyroid Cancer With Fdg Petmentioning
confidence: 99%
“…The overall diagnostic accuracy tended to be higher for lateral LNs than for central LNs. Jeong et al (2006a) reported that 5% (1/20) of the metastatic LNs in the central compartment were detected by PET. PET did not prove to be superior to US or CT (Jeong et al 2006a, Choi et al 2011b.…”
Section: Preoperative Assessment Of Thyroid Cancer With Fdg Petmentioning
confidence: 99%
See 1 more Smart Citation
“…This is usually carried out by preoperative USG of the regional neck lymph nodes in the central and lateral neck compartments. Jeong et al [45] compared the diagnostic accuracy of FDG-PET/CT as a novel staging alternative to USG for the preoperative evaluation of cervical lymph node status in patients with PTC. The final cervical lymph node status was confirmed by histopathology.…”
Section: Role Of Fdg-pet In Patients With Primary Dtcmentioning
confidence: 99%
“…The present study found that the majority of disease that was detected on a PET scan was in the cervical and mediastinal lymph nodes. In the preoperative setting, ultrasound has a higher sensitivity to detect abnormal cervical lymph nodes than PET/CT (25). Given the increased cost and radiation exposure of PET/CT compared with ultrasound, its use should be reserved for indications for which there is strong evidence supporting its utility.…”
Section: Discussionmentioning
confidence: 99%